Upaya Meningkatkan Aktivitas Dan Hasil Belajar Matematika Siswa Menggunakan Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Di SMP Negeri 14 Binjai - Aziza Fauzia Nurhaliza; Prihatin Ningsih Sagala (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
This Classroom Action Research aims to minimize the low activity and mathematics learning outcomes of Binjai 14 Public Middle School students in the matter of the Two-Variable Linear Equation System (SPDLV). The recipients of the action were class VIII 2 students at SMP Negeri 14 Binjai with a total of 32 students. The data collection technique for this action was carried out in a qualitative descriptive way through the cycle stages with two rounds where each round consisted of two meetings. The results of this study are increased activity and student learning outcomes by using the cooperative learning model of the Teams Games Tournament (TGT) type. From the results of the initial test data obtained 28 students (87,5%) of 32 students with an average of 50,29%. The results of data analysis in cycle I after the cooperative learning model of the Teams Games Tournament (TGT) type showed that the number of students who achieved mastery learning was 25 students (78,12%) out of 32 students with a class average of 75%. In cycle II, 28 students (87,5%) achieved a mastery level with a class average of 80,79%. There was an increase from cycle I to cycle II. Likewise with student activities while learning took place in cycle I, the number of students who had a percentage of activity ≥ 70% classically was 2 students (6.25%) of 32 students and at the end of cycle II it increased to 28 students (87,5%). The classical increase in activity from cycle I to cycle II was 30%. So this study concluded that through the TGT learning model it can increase students' activity and learning outcomes in mathematics.